A Systematic Approach for Identifying System Requirements from the Organization’s Business Model - Knight, Debora Mac; Araujo, Renata M.; Borges, Marcos R. S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2005)
Although it is recognized that the business model contains relevant information for obtaining system requirements, we still lack a systematic approach for discovering requirements from an existing organization’s business model. This paper proposes a method which starts from a business model, guides the software development team toward understanding business needs and identifying system requirements addressing those needs. Three case studies were conducted where the method applicability could be verified